PENGEMBANGAN MEDIA PEMBELAJARAN BULETIN PADA MATERI KIMIA UNSUR DI MADRASAH ALIYAH SWASTA (MAS) LAMNO - Noviza Rizkia (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
Learning media can be used in determining the success of students in learning where previously the learning media was still not used, and the learning process that took place in the classroom was still done manually or still using large printed books so that in fact the learning media was still lacking in use, the researchers wrote a thesis. this is entitled the development of newsletter learning media on elemental chemistry at MAS Lamno. This study aims (1) to determine the feasibility of learning media bulletin on elemental chemistry, (2) to determine student responses to learning media, (3) to determine student learning outcomes. This type of research is development (Research and Development / R & D) using the ADDIE development model through several stages, namely (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. the feasibility of the media was validated by 2 lecturers of chemistry education study program, namely media experts, material and language experts, the results of the development validation obtained an average percentage of 79.4% and for student responses and learning outcomes the data were taken from previous research, where data on student responses to newsletter learning media with an average value of 4.15 with a percentage of 82.92% is very good, while for the value of student learning outcomes the percentage is 76.47% and the student average score is 85.36% which is included in the very good category, then It can be concluded that the newsletter learning media on elemental chemistry can be used.